The concept of Islamization: some additional viewpoints in regard to Muslim upliftment around the world - Karim, A.H.M Zehadul (2013)
Islamization has now become a vastly acceptable concept among Muslims around the world, and as such, it has emerged to conceptualize a paradigmatic viewpoint to recast the episteme of human discourse corroborating the basic tenets of aquidat al tauhid (see Omar Hassan Kasule sr. 1985). From that viewpoint, it does not however, fully endorse the total reinvention of human knowledge; rather, it advocates a kind of reformative transformation of that knowledge, to make it more adjustable to the tenets of Islamic doctrine. In this respect however, I do not have any intention to redefine or re-conceptualize the issue of Islamization, rather, I want to explicate here in this paper showing an aptness of the term, and accordingly suggest that the Muslims throughout the world should explore extensive knowledge on science and technology within the guideline of their religious framework, in order to regain their past glory. We are very much aware that apart from Muslim writers, Western philosophers and statesmen from time to time, applaud Islam emphatically for its theological preaching and ideological breviary. There is always a convincing statement that the most distinctive mark of Islam is that it could unite Muslims in one world-view of Ummatic bondage, but yet we have to admit that the Muslims around the world are often disintegrated because of the disunity among themselves. Islamization should take those points into consideration, and use an additional term in its lexicon by connoting it as ‘applied aspect of Islamization’, which will include issues like upliftment and socioeconomic improvement of the ummah. Being part of the Islamization process, we may therefore aim for uniting the Muslims under the common platform to nurture ‘a good brotherhood’ based on feelings and well-being for every one of us and seeking more wisdom. This will eventually allow us to be considered as a reverent force in the global context where Islamic practices move simultaneously to generate knowledge in wider context. Accordingly, the paper suggests an integrated model which could be added as an Islamization strategy for Muslim upliftment throughout the world.